THE ROLE OF SOCIAL BUSINESS STRATEGY IN IMPROVING SMALL BUSINESS OWNER INCOME - Muh. Husriadi; Ikrar Muadsim; Deprianus Sarlis (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Social business strategy is becoming an important approach to improving business actor income small businesses facing various social and economic challenges. This research aims analyzing the role of social business strategies in supporting sustainability business small through product innovation, participation community, and sustainable income models. The method used is qualitative research with a case study approach, involving interview in-depth and observation of business actors’ small businesses implementing social business strategies. The research results show that social business strategies are effective push improvement income by integrating social and economic values through product innovative as well as involvement active community. Obstacles such as limited capital and knowledge managerial is challenges that need to be overcome to optimize results. The implications of this research emphasize importance support training management, access funding, and the use of digital technology to strengthen implementation of social business. This study contributes to the development of theory social entrepreneurship at the same time practice empowerment business sustainable small.